The Operational Baysean Approach for Finite Populations (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In this paper we discuss invariant prediction in finite populations. It is assumed that the distribution of the observable quantities is invariant under an orthogonal group of transformations.